FINANCIAL FACTORS AND MANDATORY DISCLOSURES - DIRVI SURYA ABBAS; BASUKI; IMAM HIDAYAT; RAHAYU ALPIANI (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2020)
The purpose of this study to determine the effect of Leverage, Profitability and Liquidity on mandatory disclosures in companies in the consumer goods industry sector which are listed on the Indonesia Stock Exchange (IDX). The research period used is 5 years, namely the 2014-2018 period. The population of this study includes all manufacturing companies in the consumer goods industry sector which are listed on the Indonesia Stock Exchange (IDX) for the 2014-2018 period. The sampling technique uses purposive sampling technique. Based on predetermined criteria obtained by 6 companies. The type of data used is secondary data obtained from the Indonesia Stock Exchange website. The analysis method used is panel data regression analysis. The results showed that Leverage has an effect on mandatory disclosure, and Profitability and Liquidity have no effect on mandatory disclosure.